+0  
 
0
38
2
avatar

Algebra 2 help?

Guest Sep 7, 2017
Sort: 

2+0 Answers

 #1
avatar+21 
+1

=(x^2-2xy+y^2)-9

mrlevan3  Sep 7, 2017
 #2
avatar+4480 
+3

[ (x - y) - 3 ] [ (x - y) + 3 ]

 

Note that    (a - b)(a + b)  =  a2 - b2

 

And for this problem we can say that  a = (x - y)  and  b = 3 .

 

So.....

 

[ (x - y) - 3 ] [ (x - y) + 3 ]  =  (x - y)2  -  32

 

[ (x - y) - 3 ] [ (x - y) + 3 ]  =  (x - y)2  -  9

hectictar  Sep 7, 2017

5 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details